Penyusunan Laporan Keuangan Berdasarkan Standar Akuntansi Keuangan Entitas Mikro Kecil dan Menengah (SAK-EMKM) Studi Kasus Pada UMKM Jeje Collection - Dewi Nur Azizah; Azzahra Najwa Debby Maharani; Anastasia Putri; Annisa Nurul Pebriyanti; Salwa Toha; Sri Rahayuningsih (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Business Development in Indonesia is currently running rapidly. One type of business that is currently developing in Indonesia is micro, small and medium enterprises (MSME). MSME are one of the drivers of the national economy and play an important role in the Indonesian economy because they can stimulate and improve the economy in a sustainable and sustainable manner. SAK-EMKM is the basis for preparing financial statements using primary data. From the results of research conducted at Jeje Collection MSME, it can be seen that the financial statements prepared and presented by Jeje Collection MSME are still very simple and not in accordance with SAK-EMKM because MSME owners do not understand the specific financial statement standards for MSME, after applying the Jeje Collection MSME financial statements based on SAK-EMKM as a whole, prepared and presented with the same amount. The application of financial statements in accordance with SAK-EMKM presents financial statements consisting of three components, namely the statement of financial position, income statement, and notes to financial statements (NOFS).